Intranasal naloxone rapidly occupies brain mu-opioid receptors in human subjects - Johansson, Jarkko; Hirvonen, Jussi; Lovró, Zsófia; Ekblad, Laura; Kaasinen, Valtteri; Rajasilta, Olli; Helin, Semi; Tuisku, Jouni; Sirén, Saija; Pennanen, Mirka; Agrawal, Arvind; Crystal, Roger; et al. (Neuropsychopharmacology (New York, N.Y.), 2019)
Nasal spray formulations of naloxone, a mu-opioid receptor (MOR) antagonist, are currently used for the treatment of opioid overdose. They may have additional therapeutic utility also in the absence of opioid agonist drugs, but the onset and duration of action at brain MORs have been inadequately characterized to allow such projections. This study provides initial characterization of brain MOR availability at high temporal resolution following intranasal (IN) naloxone administration to healthy volunteers in the absence of a competing opioid agonist. Fourteen participants were scanned twice using positron emission tomography (PET) and [ C]carfentanil, a selective MOR agonist radioligand. Concentrations of naloxone in plasma and MOR availability (relative to placebo) were monitored from 0 to 60 min and at 300-360 min post naloxone. Naloxone plasma concentrations peaked at ~20 min post naloxone, associated with slightly delayed development of brain MOR occupancy (half of peak occupancy reached at ~10 min). Estimated peak occupancies were 67 and 85% following 2 and 4 mg IN doses, respectively. The estimated half-life of occupancy disappearance was ~100 min. The rapid onset of brain MOR occupancy by IN naloxone, evidenced by the rapid onset of its action in opioid overdose victims, was directly documented in humans for the first time. The employed high temporal-resolution PET method establishes a model that can be used to predict brain MOR occupancy from plasma naloxone concentrations. IN naloxone may have therapeutic utility in various addictions where brain opioid receptors are implicated, such as gambling disorder and alcohol use disorder.